Village-Card: Village Accounting Educational Game - Swastika Ayuniar; Slamet Fauzan (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2024)
This research is aimed at developing Village-card learning media: Village accounting educational games that are interesting and fun, so that later it is expected to be able to liven up the atmosphere and also increase the intrinsic motivation of students. This research uses the borg and gall development method which consists of 10 steps with several stages of testing. In the test stage, this game expert received a feasibility score of 89% each by media and material experts, and the feasibility of questionnaires by research instrument experts of 78%. In the field trial stage, 23% of them strongly agreed and 59% agreed that this game was suitable for practice and as a learning tool on village accounting materials. Furthermore, to calculate the effectiveness of this game, a t-test is carried out. Based on the results of the t-test, in the paired sample test the value of Sig. (2-tailed) is 0.001 < 0.005 so it can be concluded that there is an average difference between intrinsic motivation before and after using the village card, which means there is an effect of using the village card on increasing intrinsic motivation of students.